2005
DOI: 10.1017/s1461145705005560
|View full text |Cite
|
Sign up to set email alerts
|

A NOS-III haplotype that includes functional polymorphisms is associated with bipolar disorder

Abstract: The pleiotropic messenger molecule nitric oxide (NO) has been implicated in a variety of higher CNS functions, including learning, memory, and emotionality. In the human brain, NO is predominantly formed by neuronal NO synthase (NOS-I), while the so-called 'endothelial' isoform NOS-III also contributes to NO generation. We recently reported that NOS-III knockout mice display decreased adult neurogenesis and reduced responsiveness in a learned helplessness paradigm. To examine whether NOS-III plays a role in af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
5
25
0
1
Order By: Relevance
“…We did not include an association analysis with rs2682826, because this SNP does not influence biological function. On the other hand, Reif et al [38] reported an association between the eNOS gene (NOS3) and BP patients. The levels of platelet eNOS activity in MDD patients were lower than in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include an association analysis with rs2682826, because this SNP does not influence biological function. On the other hand, Reif et al [38] reported an association between the eNOS gene (NOS3) and BP patients. The levels of platelet eNOS activity in MDD patients were lower than in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen retention is dependent upon dietary consumption of nitrogen rich foods along with lipid consumption, electrolyte stability, and mineral density. Analysis of polymorphisms of nitric oxide synthases have not yielded any conclusive evidence for their involvement in the pathogenesis of major depression (Yu et al 2003;Reif et al 2006). In a small sample of 15 subjects with major depression, decreased plasma nitric oxide metabolite levels and platelet endothelial nitric oxide synthase activity were observed (Chrapko et al 2004).…”
Section: Nitrogenmentioning
confidence: 99%
“…As revealed by immunohistochemical and autoradiographic studies, the distribution of NOS-I achieves its maximum in the cerebellum followed by the hippocampus and neocortex (Bredt and Snyder, 1989 ;Kidd et al, 1995). Another enzyme influencing NO function in the brain is the endothelial nitric oxide synthase (NOS-III) (Reif et al, 2006b). Mice lacking NOS-III show a low rate of neural stem cell proliferation, and in an animal model of depression, i.e.…”
Section: Introductionmentioning
confidence: 99%